Penerapan Algoritma K-Medoids Clustering Dalam Pembentukan Zona Cluster Vaksin Boster - Lialiyah, Siti; Andrea, Reza (Building of Informatics, Technology and Science (BITS), 2022)
The effects of the COVID-19 virus pandemic are quite bad for people's lives both in Indonesia and especially in North Sumatra. The spread of the virus is quite fast from the interaction of every community, causing the government to make policies to limit the activities of each community. In addition to policies in limiting community activities, the government also makes policies by distributing vaccines for free to every community starting from the first vaccine, the second and last vaccine is the third vaccine (booster). The purpose of the vaccine itself is to stimulate the body's antibodies to recognize the weakened virus in the vaccine. The aim of the vaccine is to slow the spread of the virus itself. The third vaccine (booster) is a complementary vaccine given by the government so that antibodies can completely inhibit a person from being affected by the COVID-19 virus. Therefore, it is necessary to accelerate the process of administering the third vaccine (booster). This can be done by forming clusters in each region. The purpose of forming clusters is to be able to identify priority areas that should be given the third vaccine (booster). Therefore we need a technique that is able to group/cluster the third vaccine administration zone (booster). One technique that can be used is the K-Medoids Algorithm. The expected results of the research using the K-Medoids Algorithm are able to form a cluster zone which will later be able to find out which areas are the priority for giving the third vaccine (booster).